A escuta ao abuso sexual: o psicólogo e o sistema de garantia de direitos da criança e do adolescente sob visão da psicanálise - Marques, Margarete dos Santos (2006)
This project intends to articulate, based on a psychoanalytic referential, some aspects of existence and experiences of professionals with ambiguities and contradictions related to the function of psychologists who work in the system of assurance of children and adolescents rights taking care of cases in child sexual abuse. We ve approached the concept of child, mainly how this child became a central character in the social scene carrying the ideal of a good future. We must point out how Brazilian society has mobilized itself to consider a child as an individual with rights, through the promulgation of the Child and Adolescence Act. We ve reflected on several concepts of violence, sexual abuse, incest, listening to contradictions that prowl this segment, due to different theories and epistemological and political positioning of authors. And observing the impossibility of a consensus in the use of terminology to name the child sexual abuse phenomena. We ve interviewed psychologists who work in services of protection, in order to investigate how they experienced the theme, their conflicts, anguishes and pains, their values as well as ethical, moral and religious formulations. Thus we ve faced a demand of justice for the psychologist to produce proof to support the legal decision in the conviction of the alleged abuser. In the interview s analyses we ve raised several questions to create a movement not in search of absolute truths, but yet, to dilute some questions so that other questions can be asked through talks with authors to discuss the interface between Psychology/Psychoanalysis and the Law. We ve concluded that it s necessary to promote reflections in universities and social classes so that the psychotherapeutic treatment is taken by the patient as a right and not as a duty, and that the psychologist ethics be considered in the dialogue with the law